Stress Granules and Processing Bodies in Translational Control - Ivanov, Pavel; Kedersha, Nancy; Anderson, Paul (Cold Spring Harbor perspectives in biology, 2019)
Stress granules (SGs) and processing bodies (PBs) are non-membrane-enclosed RNA granules that dynamically sequester translationally inactive messenger ribonucleoprotein particles (mRNPs) into compartments that are distinct from the surrounding cytoplasm. mRNP remodeling, silencing, and/or storage involves the dynamic partitioning of closed-loop polyadenylated mRNPs into SGs, or the sequestration of deadenylated, linear mRNPs into PBs. SGs form when stress-activated pathways stall translation initiation but allow elongation and termination to occur normally, resulting in a sudden excess of mRNPs that are spatially condensed into discrete foci by protein:protein, protein:RNA, and RNA:RNA interactions. In contrast, PBs can exist in the absence of stress, when specific factors promote mRNA deadenylation, condensation, and sequestration from the translational machinery. The formation and dissolution of SGs and PBs reflect changes in messenger RNA (mRNA) metabolism and allow cells to modulate the proteome and/or mediate life or death decisions during changing environmental conditions.